Impact of tenofovir, lamivudine, and dolutegravir on liver function in HIV-positive individuals in Southern Nigeria - Odekunle Bola Odegbemi; Mathew Folaranmi Olaniyan; Musa Abidemi Muhibi (Golestan University Of Medical Sciences, 2024)
Background: Antiretroviral therapy (ART) has transformed HIV management, but concerns regarding liver toxicity persist, particularly with the use of reverse transcriptase inhibitors (RTIs) and integrase strand transfer inhibitors (INSTIs). This study aims to assess the impact of tenofovir/lamivudine/dolutegravir (TLD) therapy on liver function in HIV-positive individuals at a military hospital in southern Nigeria. Methods: We conducted a cross-sectional study involving 170 participants: 120 HIV-positive individuals on TLD and 50 HIV-negative controls, matched for age, sex, socioeconomic status, and ethnicity. Data were collected through questionnaires and blood sampling. Plasma levels of liver function markers, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), glutathione S-transferases (GSTs), total protein (TP), and albumin (Alb), were analyzed using relevant biochemical methods. We conducted a statistical analysis using SPSS version 23, with significance set at p < 0.05. Results: Significant differences were observed in AST, TP, Alb, and GST levels between HIV-positive individuals on TLD and HIV-negative controls. HIV-positive subjects exhibited lower AST and Alb levels but higher TP and GST levels. Further analysis revealed correlations between age, gender, and liver enzymes, highlighting the complex interplay between HIV, liver function, and treatment outcomes. Conclusion: The results suggested that decreased AST levels may indicate a protective effect of TLD on liver integrity, while ALT activity showed minimal impact. Changes in TP, Alb, and GST levels emphasize the importance of monitoring hepatic function and detoxification pathways in HIV-positive individuals on TLD therapy.